Deagglomeration of aerosil in polishing suspension for chemical-mechanical polishing of sapphire - Vovk, E.A. (Functional Materials, 2015)
Studied is the influence of pH, surface-active substances and ultrasonic dispersing on the degree of deagglomeration of aerosol in the polishing suspensions used for CMP of sapphire, the removal rate and the optical quality of the surface at polishing. Ultrasonic dispersing makes it possible to obtain silica sol. It is established that the addition of high-molecular compounds with the functional groups OH favors deagglomeration of aerosil, raises the removal rate and allows to obtain the sapphire surface with the optical quality 20/10-40/20 according to the USA standard MIL-0-13830.